Conditioned medium from stimulated mononuclear leucocytes potentiates the ability of human neutrophils to damage human articular cartilage. Issue 1 (January 1988) - Bates, E J; Kowanko, I C; Ferrante, A
Abstract : Human neutrophils were able to degrade proteoglycan and inhibit its synthesis when incubated with human articular cartilage coated with heat aggregated immunoglobulin G. These effects were potentiated when culture medium conditioned by mononuclear leucocytes stimulated with killed Staphylococcus aureus was also present during the incubations. Neutrophils preincubated with this conditioned medium and washed before incubation with cartilage also showed an increased ability to degrade proteoglycan and inhibit its synthesis. The percentage of neutrophils binding to cartilage was significantly increased in the presence of this conditioned medium.